2023
DOI: 10.1177/03000605231175365
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial scratch injury in infertile women undergoing in vitro fertilization cycles: a systematic review and meta-analysis

Abstract: Objective This study aimed to evaluate the effect of endometrial scratch injury (ESI) in infertile women undergoing in vitro fertilization (IVF). Methods We screened MEDLINE, CENTRAL, EMBASE, Web of Science, and the Cochrane Central Register from inception to April 2023 using keywords related to endometrial scratch, implantation, infertility, and IVF. We included 41 randomized, controlled trials of ESI in IVF cycles (9084 women). The primary outcomes were the clinical pregnancy, ongoing pregnancy, and live bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Findings from this study suggest that patients who underwent endometrial scratch using the Shepard catheter have significantly lower pain scores compared to those who underwent the Pipelle. Low to moderate pain and discomfort are commonly reported by patients who received the Pipelle for endometrial biopsy (7,8,10). However, to our knowledge, no prior studies have assessed pain scores and ART outcomes using the Shepard catheter compared to the standard Pipelle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from this study suggest that patients who underwent endometrial scratch using the Shepard catheter have significantly lower pain scores compared to those who underwent the Pipelle. Low to moderate pain and discomfort are commonly reported by patients who received the Pipelle for endometrial biopsy (7,8,10). However, to our knowledge, no prior studies have assessed pain scores and ART outcomes using the Shepard catheter compared to the standard Pipelle.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review of 12 studies involving 3,382 participants undergoing their first cycle of IVF, endometrial scratch had no significant effect on clinical pregnancy rates, and any minimal observed effects on implantation rates was deemed unreliable (9). However, a recent meta-analysis of 41 randomized control trials found that endometrial scratch improved implantation and clinical pregnancy rates in patients undergoing IVF when conducted during the follicular or luteal phase (8). Consequently, our study highlights the importance of optimizing endometrial scratch procedures to reduce patient discomfort, a valuable clinical consideration when the efficacy of specific techniques appears limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation